Implementasi Penanaman Nilai-Nilai Kedisiplinan Siswa Melalui Kegiatan Shalat Dhuha Berjamaah - Nadliroh, Umi; Sudarti, Sudarti; Amin, Muhamad; Adib, Akhmad Jauharul (AL-BURHAN, 2024)
This research aims to explore the implementation of discipline values in students of Madrasah Aliyah (MA) Miftahut Thullab in Cengkalsewu Pati, through communal Dhuha prayer activities. Dhuha prayer is considered a potential means to instill discipline in students. The research utilizes observation and interviews with students, educators, and administrators of MA Miftahut Thullab. The findings indicate that communal Dhuha prayer activities have been successfully integrated into the daily lives of students and have positively impacted their discipline. The active role of educators and support from the school environment are key factors in the success of this implementation.Keywords: Dhuha prayer, Implementation of values, Religious education, Student discipline, MA Miftahut Thullab.